Spiders - Gilpin, Rebecca; Gilpin, Rebecca Rebecca J.; Usborne Publishing Ltd. (London Usborne Publishing Ltd., 2002)
Introduces spiders, including where they live, how they spin webs, and how they catch prey. Written in simple language with vivid illustrations to help young readers develop reading confidence and learn fascinating facts about spiders.
Includes index. Usborne Beginners series is designed for early readers and features large, readable font, simple sentences, and informative illustrations.
Primary level readers.
Keywords: Spiders -Arachnids-Nature study